APPROACH AND UNDERSTANDING OF SURGICAL TRAINEES TOWARDS THE USE OF UNIVERSAL ACS-NSQIP SURGICAL RISK CALCULATOR, AND CLINICAL DATA KEEPING AND ITS AUDIT - JAWAID , B; ZAHEER , F; SHARAFAT , MA; SALMAN , S; KOMAL, DR; SHAHAB , H (Biological and Clinical Sciences Research Journal, 2024)
Clinical audit methods and surgical risk calculators are paramount in advancing surgical protocols and enhancing patient outcomes. The objective is to assess surgical trainees' approach and understanding of using the Universal ACS-NSQIP Surgical Risk Calculator and clinical data keeping and its audit to improve surgical practices and patient outcomes. A cross-sectional study was administered among 71 surgical trainees at Dr. Ruth K. M. Pfau Civil Hospital Karachi to assess their understanding, perspectives, and behaviors about using the risk calculator and procedures for data management. To gather this information, a questionnaire-based survey was utilized to collect data, which was analyzed via SPSS. The participants displayed limited familiarity (9.9%, n=7) and implementation (0%) of the ACS-NSQIP Surgical Risk Calculator in the clinical practice of surgical trainees. Despite most participants expressing confidence in the calculator's reliability (71.4%) and advocating for its integration into surgical practice (85.7%), its utilization remains non-existent. Moreover, while every participant acknowledged the significance of mantaining patient records and conducting audits, only 22.5% reported participating in clinical data audits. Furthermore, most surgical residents relied on clinical intuitions and conventional sources such as textbooks for patient consultations. There is a notable gap between the comprehension and utilization of the Universal ACS-NSQIP Surgical Risk Calculator among surgical residents. This research emphasizes the necessity to comprehend and utilize for incorporating evidence-based instruments such as the Universal ACS-NSQIP Surgical Risk Calculator and implement rigorous data management and review protocols to cultivate a culture of quality enhancement and optimize patient outcomes. This can be attained through initiatives such as educational programs, enhanced availability of resources, and improved assistance for the compilation and evaluation of data.